Peran Lingkungan Eksternal yang ada di Lembaga Pendidikan: Kajian Studi Literatur Manajemen Strategik - Hesti Kusumaningrum; Najwa Fithriyah; Calvin Gilang Nugraha; Muhammad Fata Rayyan Ghafur (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
the external environment has an important influence on the sustainability of an organization. The purpose of this research is to analyze and describe the role of the external environment in educational institutions. The research method used in this research is a literature study approach, in other words, the research was conducted without a research location, but all data was taken through previous studies in the form of books and scientific articles relevant to the research theme. Data collection techniques in this study used documentation, with data analysis techniques in the form of data reduction, data presentation, and conclusion drawing. The results found that the external environment helps educational institutions to understand external factors that can affect their performance and success. SWOT is used as a tool to evaluate the strengths, weaknesses, opportunities, and threats of educational institutions. The external environment in organizations is divided into two: micro (small scope) involving competitors and partnerships, and macro (general scope) involving economic, political/legal, socio-cultural, technological, and global factors. The steps used in the analysis process involve scanning, monitoring, forecasting, and assessing.